Sistem Monitoring Jumlah Pengunjung Tingkat Kebisingan Dan Kendali Intensitas Cahaya Perpustakaan Terintegrasi Internet Of Things - Nirwan Sinuhaji (STMIK Budi Darma, 2023)
The library is a place to seek information and knowledge through reading and according to expert Prof. Sulistyo Basuki A library is a room or building used to store books and other publications which are usually stored based on a certain arrangement for use by readers and not for sale. This tool for detecting the number of visitors, noise levels and controlling light intensity in the library was created with the aim of assisting librarians in organizing activities in the library and creating a comfortable and conducive library situation. This tool utilizes the Internet of Things Platform to view data on the number of visitors, noise levels and light intensity controls which are connected via the officer's smartphone. This tool will detect the number of visitors that exceeds capacity, detect sound that exceeds the set limits, and light intensity that is not appropriate for the library. This tool will convey information in the form of a warning sound produced by the Driver Buzzer